PROMOTION ON BOOKS OF HEAVEN ON THE EARTH OF SRIWIJAYA BY USING SOCIAL MEDIA - Benget Simamora; Yessy Yerta Situngkir; Engga Saputra (Politeknik Negeri Media Kreatif, 2019)
Book promotion is the most important part in marketing activities.in the business world,promotional activities are carried to support marketing and sales activities â€œSurga di Bumi Sriwijayaâ€. In this finnal project report,the writer has the goal of explaining how to use Instagram and Facebook social media to promote the bookâ€™s script â€˜Surga di Bumi Sriwijayaâ€ by novice writers. The author uses the promotional mix theory is the Interactive internet marketing. Social media used by the authors are Instagram and Facebook. In final project,the author uses Quantitative descriptive method that explains in detail and validity the promotion of the book â€œSurga di Bumi Sriwijayaâ€ Using social media Istagram and Facebook is an easy and inexpensive effective step for novice writers who are introducing works accroding to target market already determine